Integrating solar PV (photovoltaics) in utility system operations: Analytical framework and Arizona case study. (1st June 2015) - Wu, Jing; Botterud, Audun; Mills, Andrew; Zhou, Zhi; Hodge, Bri-Mathias; Heaney, Mike
Abstract: A systematic framework is proposed to estimate the impact on operating costs due to uncertainty and variability in renewable resources. The framework quantifies the integration costs associated with sub-hourly variability and uncertainty as well as day-ahead forecasting errors in solar PV (photovoltaics) power. A case study illustrates how changes in system operations may affect these costs for a utility in the southwestern United States (Arizona Public Service Company). We conduct an extensive sensitivity analysis under different assumptions about balancing reserves, system flexibility, fuel prices, and forecasting errors. We find that high solar PV penetrations may lead to operational challenges, particularly during low-load and high solar periods. Increased system flexibility is essential for minimizing integration costs and maintaining reliability. In a set of sensitivity cases where such flexibility is provided, in part, by flexible operations of nuclear power plants, the estimated integration costs vary between $1.0 and $4.4/MWh-PV for a PV penetration level of 17%. The integration costs are primarily due to higher needs for hour-ahead balancing reserves to address the increased sub-hourly variability and uncertainty in the PV resource. Highlights: We propose an analytical framework to estimate grid integration costs for solar PV. Increased operating costs from variability and uncertainty in solar PV are computed. A case study of a utility in Arizona is conducted. Grid integration costs are found in the $1.0–4.4/MWh range for a 17% PV penetration. Increased system flexibility is essential for minimizing grid integration costs.